2013
DOI: 10.1055/s-0033-1333899
|View full text |Cite
|
Sign up to set email alerts
|

Far Cortical Locking Technology for Fixation of Periprosthetic Distal Femur Fractures: A Surgical Technique

Abstract: Far cortical locking screws have been shown to form greater amounts of callus in ovine studies when compared to traditional locking plates. These screws have recently become available for clinical use. This article describes the indications and surgical technique for far cortical locking screws, with a focus on distal femur periprosthetic fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Although the results of periprosthetic supracondylar femoral fractures are improving due to the use of locking plates, surgical treatment of this fracture in osteoporotic bone with a short distal segment remains challenging [11, 13, 16, 25, 26]. Several biomechanical studies [6, 20] have reported that less‐invasive stabilization systems may not be indicated for comminuted fractures because of the great stress movements between fragments, resulting in high stress and strain conditions and susceptibility to catastrophic failure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of periprosthetic supracondylar femoral fractures are improving due to the use of locking plates, surgical treatment of this fracture in osteoporotic bone with a short distal segment remains challenging [11, 13, 16, 25, 26]. Several biomechanical studies [6, 20] have reported that less‐invasive stabilization systems may not be indicated for comminuted fractures because of the great stress movements between fragments, resulting in high stress and strain conditions and susceptibility to catastrophic failure.…”
Section: Discussionmentioning
confidence: 99%
“…Far cortical locking (FCL) screws can be seen as a new frontier in traumatology. Combined with locking plates, FCL screws show greater elasticity of the construct, promoting callus formation 40 . Moazen et al demonstrated in 2016 that FCL screws guarantee and increase fracture site micro-movements, but also the stability of the PPF synthesis under axial and torsional loads.…”
Section: Discussionmentioning
confidence: 99%
“…[60] Periprosthetic femur fractures are another area where utility of these plates can be instrumental. [61] Various advantages make the FCL an attractive option for selected cases but availability and cost seem to be a problem in their widespread use in developing countries.…”
Section: Screw Modifications Within Plate Constructsmentioning
confidence: 99%